A Study of Diasporic Consciousness and Experience in Arranged Marriage in Indian English Fiction: Exploring the Complexities of Identity and Cultural Adaptation (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Diaspora is synonymous with new writing of migration such writing springs from an exhaustive running commitment with the host nation with respect to the outsider. Settler writing catches the twisting experience of movement in an alien nation for the migrant. The essential fixations for the new writing of migrant incorporate sentimentality and additionally coerce for the nation of origin and intergenerational clashes between settler guardians and American conceived kids. India is comprise of culture situated society, where man centric mentality is exceptionally conspicuous which does not give proportionate place to women who possesses close about portion of the populace yet at the same time attempting to be perceived as a person God has made with minimal diverse attributes yet not as a weaker variant of man. With the developing mindfulness and instruction different works comprising the topics of enslavement, difficulties in altering in post and pre-marriage status, aggressive behavior at home, social molding and the changing picture of women in the public eye by the writers like Anita Desai, Shashi Deshpande, Manju Kapoor and numerous others have turned out to be prevalent yet the contemporary writing is affected by the effect of globalization, artistic works are currently crossing the limits of countries and societies. Chitra Banerjee Divakaruni is a productive writer who has composed many articles, sonnets, short stories and novels. In her works she has offered voice to foreigner Indian women. Indian conceived novelist Chitra Banerjee Divakaruni presently lives in Houston, Texas. Her novels give new points of view to contemporary women's writing. In them we have women who either live abroad or happen to visit India. These women are no uncertainties molded by the Indian childhood however have transcended the customary limitations. They are torn amongst old and new qualities.